Enhancing Student Engagement in Islamic Religious Education Through a Finite-State Machine and Guided Inquiry-Based Serious Game - Marandy, Yuniar Setyo; Nugroho, Fresy; Kusumawati, Ririen; Handayani, Tuti; Marudin, Marudin (Didaktika Religia, 2025)
This study aims to develop interactive learning media in the form of a serious game based on Finite State Machine (FSM) and guided inquiry approach to improve student engagement and understanding of Islamic Education material, especially the exemplary story of Ashabul Kahfi. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The game was developed with enemy characters based on Finite State Machine (FSM), consisting of three main conditions: patrol, pursuit, and return to the path, to create dynamics and challenges in educational games. Fourth-grade elementary school students were the main subjects in testing the effectiveness of the media, which involved pre-tests and post-tests to measure learning outcome improvement, as well as validation by subject matter and media experts. The results showed that the developed media met the feasibility criteria with a subject matter expert validation score of 3.5 and a media expert validation score of 4.0, as well as an N-Gain value of 0.53, which is in the moderate category. These findings indicate that the combination of FSM and guided inquiry methods in serious games can create an interactive, enjoyable, and effective learning experience that increases student engagement and critical thinking skills in PAI material. The research results recommend this media as an alternative for interactive digital learning at the elementary school level.